MILLIY MANFAATLARDAN KELIB CHIQQAN HOLDA UMBUMBASHARIY MUAMMOLARGA YONDASHISH: NAZARIY ASOSLAR VA AMALIY YO‘NALISHLAR (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article provides a scientific and theoretical analysis of the relationship between national interests and global challenges. In the context of globalization, addressing universal human problems while safeguarding national interests has become increasingly important for states. The study examines national-interest-based approaches to global issues such as security, environmental sustainability, social inequality, and sustainable development. Particular attention is given to the balance between international cooperation and national sovereignty.